Peningkatan Hasil Belajar Fikih Materi Puasa Dengan Model Pembelajaran The Power Of Two Di MTsN 7 Tabalong - Muhammad Yusran; Alfisah Iriani; Hasan Hasan (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
This research was conducted because of the desire to improve student learning outcomes in fiqh subjects. The type of research used is two-cycle class action research. To be able to determine student learning outcomes, tests, observations, documentation, and reflections were carried out. The purpose of this study was to determine whether there was an increase in student learning outcomes. The subject of the research was class VIII C MTsN 7 Tabalong students in the 2023/2024 academic year totalling 32. The object of research on Fiqh learning outcomes on fasting material through The Power Of Two methods. This study found that student learning outcomes increased, as evidenced by the value of student learning outcomes starting from before the action, students who completed the KKM were 12 students, or 36%, and those who were not completed were 20 students or 64%. In cycle I, the percentage of students who achieved KKM was 25 students or 80% and those who were not complete were 7 students or 20%. Furthermore, in cycle II the percentage of students who have reached the KKM score is 32 students or 100%.